Wave‐Driven Flow Along a Compact Marginal Ice Zone. Issue 3 (5th February 2021) - Thomson, Jim; Lund, Björn; Hargrove, John; Smith, Madison M.; Horstmann, Jochen; MacKinnon, Jennifer A.
Abstract: Observations of surface waves and ice drift along a compact sea ice edge demonstrate the importance of waves in a marginal ice zone. An analytic model is presented for the along‐ice drift forced by the radiation stress gradient of oblique waves. A momentum balance using quadratic drag to oppose the wave forcing is sufficient to explain the observations. Lateral shear stresses in the ice are also evaluated, though this balance does not match the observations as well. Additional forcing by local winds is included and is small relative to the wave forcing. However, the wave forcing is isolated to a narrow region around 500‐m wide, whereas the wind forcing has effects on larger scales. The simplistic drag is assessed using observations of shear and turbulent dissipation rates. The results have implications for the shape and evolution of the ice edge, because the lateral shear may be a source of instabilities. Plain Language Summary: Ocean surface waves rapidly get smaller when traveling from open water into sea ice. Although waves in sea ice do not break, there are some similarities to waves traveling through the surf zone, which lose most of their energy and momentum before reaching the shore. Here, the wave momentum is transferred to the sea ice and can cause strong ice drift. In the case of waves arriving at an oblique angle to the ice edge, the ice drift is directed along the ice edge, similar to alongshore currents in the surf zone. Continuing the surf‐zone analogy, the wave energy is transferred into turbulence below the water (ice) surface. Finally, there are fluctuations in the ice edge shape that may be related to this wave forcing. Key Points: Obliquely propagating surface waves drive flow (ice drift) along a marginal ice zone Gradients in the waves provide the momentum for the ice drift, which is opposed by ice‐ocean stress in a simple model Instabilities in the strongly sheared ice drift may cause fluctuations in the ice edge shape